Using Predicted Cardiovascular Disease Risk in Conjunction With Blood Pressure to Guide Antihypertensive Medication Treatment - Muntner, Paul; Whelton, Paul K (Journal of the American College of Cardiology, 2017)
Using cardiovascular disease (CVD) risk instead of or in addition to blood pressure (BP) to guide antihypertensive treatment is an active area of research. The purpose of this review is to provide an overview of studies that could inform this treatment paradigm. We review data from randomized trials on relative and absolute CVD risk reduction that can occur when antihypertensive treatment is guided by CVD risk. We also review population-level data on using CVD risk in conjunction with BP to guide antihypertensive treatment, the broad distribution in CVD risk for people with similar BP levels, and the use of CVD risk for guiding antihypertensive treatment among subgroups including older adults, young adults, and those with diabetes mellitus or chronic kidney disease. In addition, we review potential challenges in implementing antihypertensive treatment recommendations that incorporate CVD risk. In closing, we provide recommendations for using CVD risk in combination with BP to guide antihypertensive treatment.